The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/clr.12650
|View full text |Cite
|
Sign up to set email alerts
|

Dental floss as a possible risk for the development of peri‐implant disease: an observational study of 10 cases

Abstract: In case of exposed rough surfaces of the dental implant, the peri-implant conditions may be jeopardized by the application of dental floss, and hence, the utilization of interproximal brushes or toothpicks may be preferred for daily home care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Here, it was shown that dental floss may be torn on exposed rough surfaces of implants, promoting plaque retention. Therefore, flossing was identified as a potential risk factor for peri‐implant health (van Velzen, Lang, Schulten, & Ten Bruggenkate, ). However, this disadvantage with flossing could not be confirmed in the current study due to its in vitro design with non‐exposed rough implant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it was shown that dental floss may be torn on exposed rough surfaces of implants, promoting plaque retention. Therefore, flossing was identified as a potential risk factor for peri‐implant health (van Velzen, Lang, Schulten, & Ten Bruggenkate, ). However, this disadvantage with flossing could not be confirmed in the current study due to its in vitro design with non‐exposed rough implant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Leftover titanium fragments released from dental implants after the use of an ultrasonic instrument have been shown to introduce foreign bodies to the peri-implant space, which may aggravate the situation. 7,8 Leftover titanium fragments released from dental implants after the use of an ultrasonic instrument have been shown to introduce foreign bodies to the peri-implant space, which may aggravate the situation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, suppuration is logically and statistically a sensitive indicator of bone turnover . In this scenario, it must be noted that, if detected in early stages where bone resorption has not occurred yet, it might be a consequence of a foreign body reaction (i.e., residual cement or dental floss remnants) or biofilm …”
Section: Introductionmentioning
confidence: 99%
“…24 In this scenario, it must be noted that, if detected in early stages where bone resorption has not occurred yet, it might be a consequence of a foreign body reaction (i.e., residual cement or dental floss remnants) or biofilm. 25,26 Therefore, although the use of clinical parameters with radiological proof of bone changes represents a "gold standard", the diagnostic value of clinical parameters of implants is still controversially reported and not well defined. 10 Standardization of the diagnostic parameter implies well defined methodological approach intended to estimate the accuracy, precision, sensitivity and specificity of the parameter to distinguish different states of the target tissue or organ.…”
Section: Introductionmentioning
confidence: 99%